Understanding the Impacts of Research Synthesis. Issue 86 (August 2018) - Wyborn, Carina; Louder, Elena; Harrison, Jerry; Montambault, Jensen; Montana, Jasper; Ryan, Melanie; Bednarek, Angela; Nesshöver, Carsten; Pullin, Andrew; Reed, Mark; Dellecker, Emilie; Kramer, Jonathan; et al.
Highlights: Synthesis research is gaining prominence in the science policy landscape. There has been little empirical examination of the impacts of these initiatives on policy and practice. This paper reviews 10 case studies from within biodiversity conservation and natural resource management from around the world. A novel conceptual framework is used to assess the impacts of, and assumptions underpinning the research synthesis. Findings suggest that research synthesis is having various types of impacts on policy and practice. Abstract: Research synthesis is the integration of existing knowledge and research findings pertinent to an issue. The aim of synthesis is to increase the generality and applicability of those findings and to develop new knowledge through the process of integration. Synthesis is promoted as an approach that deals with the challenge of öinformation overload', delivering products that further our understanding of problems and distil relevant evidence for decision-making. However, despite the increasing prominence of synthesis efforts in the science and policy landscape, we know very little about the impacts these initiatives have on research, policy and practice and the assumptions underpinning how they will lead to change. This paper presents a framework for considering the conceptual, strategic, instrumental and network-based impacts of research synthesis on policy. This framework provides insight into the range of underlying assumptions and impacts on policy and practice from 10 case studies of research synthesis related to contemporary sustainability challenges. Findings suggest that research synthesis is having diverse impacts on research, policy and practice including creating a new understanding of problems, establishing new networks, and contributing to changes in policy and practice. These impacts emerged across a range of contexts, synthesis methods, assumptions and operating models. This suggests that there is no single öcorrect way' to design research synthesis for impact, but rather a need to tailor the approach for the context of intended use.